Pengaruh Program Tahfidzul Qur’an Terhadap Pembentukan Karakter Qur’ani Santri Pondok Pesantren Tahfidzul Qur’an Bahrusysyifa’ Lumajang - Salsabila, Farah; Rofi, Sofyan; Huda, Hairul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
The Tahfidzul Qur'an program in Indonesia is growing rapidly as an innovation in Islamic education that not only improves memorization of the Qur'an, but also forms the Qur'anic character of students. Islamic boarding schools have a strategic role in instilling the values of religiosity, discipline, responsibility, and hard work in order to face moral challenges in the modern era. This study aims to determine the effect of the Tahfidzul Qur'an program on the formation of the Qur'anic character of students at the Tahfidzul Qur'an Boarding School Bahrusysyifa' Lumajang. The research method used is quantitative with a population of 92 students. Data were collected through questionnaires and analyzed using validity, reliability, normality, linearity, and hypothesis tests with SPSS 27. The results showed that the Tahfidzul Qur'an program had a significant effect on the formation of the Qur'anic character of students. Hypothesis testing with a simple linear regression test produced a Tcount value = 7,675 > Ttable = 2,632, so that Ha was accepted and H0 was rejected. The R value = 0.629 indicates a strong relationship between the two variables, while R² = 0.396 indicates that 39.6% of the variation in Qur'anic character is influenced by the Tahfidzul Qur'an program, while 60.4% is influenced by other factors.